COST OF IMPROVING THE LEASING RELATIONSHIP - Inamov Sardor Abdusalomovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. This article examines the existing problems in improving the activities of leasing companies and developing the sector in Uzbekistan. Also, the importance of regulatory and legal documents aimed at the development of leasing activity was highlighted by our government. In addition, effective suggestions and recommendations were given for the existing problems in the development of the activity of leasing companies.